Alcohol and violence in marital relations: A qualitative study with couples - Feijó, Marianne Ramos [UNESP]; Noto, Ana Regina; da Silva, Eroy Aparecida; Locatelli, Danilo Polverini; Camargo, Mário Lázaro [UNESP]; Gebara, Carla Ferreira de Paula (Universidade Estadual de Maringa, 2016)
This qualitative and descriptive study aimed to understand the relation between the alcohol consumption and the violence expansion, in the relationship of couples made up by, at least, one partner with alcohol dependence. Semi-structured interviews with 10 couples were done, which were transcribed and submitted to the content analysis. All the couples reported marital violence related to alcohol use. Violence, mainly verbal and physical ones, was committed by both partners and it became worse due to increase of amount of alcohol ingestion. Other relational and professional difficulties, associated to continuous use of alcohol, were reported, in addition to the history of substance use and violence in the origin families of the participants. This study makes evident the complexity of the marital violence associated to the alcohol dependence, which must be considered for the prevention programs, interventions and the couple guiding - as a system that requires full attention.
Keywords: Alcohol abuse; Marriage; Violence